The third pink book : a global view of lesbian and gay liberation and oppression - Hendriks, Aart; Tielman, Rob; van der Veen, Evert (Buffalo : Prometheus, 1993)
Fonds Suzan Daniel (FSD)
Engels
Monografie
Keywords: homoseksualiteit; lesbische vrouwen